PERANCANGAN BOARD GAME EDUKATIF TENTANG PEDULI LINGKUNGAN UNTUK ANAK USIA 7-12 TAHUN - DEDE JORDI, Dini Faisal, S.Ds., M.Ds., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The lack of a caring attitude towards the environment causing pollution and environmental damage is the main reason the authors designed an educational game about caring environment for early childhood, especially children aged 7-12 years. Form of the game that will be made in the form of board game, which aims to be easy to attract children, especially children of 7-12 years of age at the time the child really enjoys a media that is packaged in a game. In addition to the game board will be supported by several other media that help the major media to introduce the subject to the target audience such as packaging, rulebook, calendars, key chains, pins, clocks and stickers. The methodology used is the approach 5w + 1h which serve as the basic concept of problem solving that is what, who, when, where, why and how. The purpose of the analysis 5W + 1H is to illustrate the results of analysis used as the basis or foundation for preparing the objective and strategy in the making. And then, all aspects are summarized in the board game of Bumi